2016
DOI: 10.1159/000452741
|View full text |Cite
|
Sign up to set email alerts
|

The VEGFR Inhibitor Cediranib Improves the Efficacy of Fractionated Radiotherapy in a Colorectal Cancer Xenograft Model

Abstract: Background/Purpose: Radiotherapy (RT) increases local tumor control in locally advanced rectal cancer, but complete histological response is seen in only a minority of cases. Antiangiogenic therapy has been proposed to improve RT efficacy by “normalizing” the tumor microvasculature. Here, we examined whether cediranib, a pan-vascular endothelial growth factor (VEGF) receptor tyrosine kinase inhibitor, improves microvascular function and tumor control in combination with RT in a mouse colorectal cancer (CRC) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have shown that local radiotherapy causes a stronger expression of angiogenic factors than anti-angiogenic factors and disturbs the configuration imbalance of VEGFs in the vascular bed of the metastatic site, which then results in outbreak growth of dormant metastatic tumors [ 24 , 25 ]. Adjuvant applications of the exogenous VEFGR inhibitor cediranib after radiotherapy restored tumor inhibition, and studies have shown that using angiogenesis inhibitors to target the VEGF pathway or knocking out the VEGF gene in mouse models with pancreatic cancer or glioblastoma has anti-cancer therapeutic effects by reducing the tumor volume and prolonging survival, but the two actions change tumor phenotypes and enhance tumor invasion and metastasis [ 26 28 ]. The discontinuation of VEGF inhibitors still enhances the tumor invasion, suggesting that this treatment increases the persistence of tumor invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that local radiotherapy causes a stronger expression of angiogenic factors than anti-angiogenic factors and disturbs the configuration imbalance of VEGFs in the vascular bed of the metastatic site, which then results in outbreak growth of dormant metastatic tumors [ 24 , 25 ]. Adjuvant applications of the exogenous VEFGR inhibitor cediranib after radiotherapy restored tumor inhibition, and studies have shown that using angiogenesis inhibitors to target the VEGF pathway or knocking out the VEGF gene in mouse models with pancreatic cancer or glioblastoma has anti-cancer therapeutic effects by reducing the tumor volume and prolonging survival, but the two actions change tumor phenotypes and enhance tumor invasion and metastasis [ 26 28 ]. The discontinuation of VEGF inhibitors still enhances the tumor invasion, suggesting that this treatment increases the persistence of tumor invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in colorectal cancer xenografts have demonstrated that inhibition of the VEGF receptor (VEGFR) with concomitant fractionated RT resulted in normalization of vasculature and improved tumor control compared to RT or VEGFR-inhibition alone (129). Hyperfractionated RT is currently being combined with bevacizumab in glioblastoma patients and with sorafenib (a protein kinase inhibitor targeting VEGFR) in patients with pancreatic cancer (NCT00884741, NCT00375310).…”
Section: Using Radiotherapy To Enhance Responses To Immunotherapy In mentioning
confidence: 99%
“…However, RT also inhibits antitumor immunity by facilitating the development of immune suppressive cells, such as T regulatory cells (Tregs) (31), tolerogenic and immune suppressive dendritic cells (DC) (32), tumor-associated macrophages (TAMS) (33), tumor-associated neutrophils (TANs) (34), and MDSC (24), via a series of soluble molecules such as TGFβ (35), adenosine (36), VEGFA (37), CSF1 (24), and CCL2 (38). It is beyond the scope of this article to discuss all of these mechanisms, so the below discussion focuses on MDSC, which are present in virtually all cancer patients and are universally considered a major obstacle to cancer immunotherapies.…”
Section: Radiotherapy Activates the Immune System But Also Drives Immmentioning
confidence: 99%